Mitos Orang Kalah: Orang Laut dan Pola Pemukimannya - Edi Indrizal (Antropologi Indonesia, 2000)
In this article, the author argues for the inappropriateness of the government's policy and approach in its efforts to 'develop' the indigenous people who have been categorized as 'masyarakat terasing'. Through his analysis on the program of Pembinaan Kesejahteraan Masyarakat Terasing (PKMT), the author assumes that the program has failed. He examines the failure by looking closely at the livelihood of Orang Laut in Indragiri Hilir, the fishermen, who used to live collectively along the seashore and spend most of their time in boats. They refused to stay in the resettlement village which was provided by the government who did not base its program on the social-cultural-economic reality.